The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/chem.201500192
|View full text |Cite
|
Sign up to set email alerts
|

“(Diphosphine)Nickel”‐Catalyzed Negishi Cross‐Coupling: An Experimental and Theoretical Study

Abstract: The use of a strongly donating "(bis-dialkylphosphine)Ni" fragment promotes the catalytic coupling of a large range of ArCl and ArZnCl derivatives under mild conditions. Stoichiometric mechanistic investigations and DFT calculations prove that a Ni(0) /Ni(II) cycle is operative in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…It is important to note that previous mechanistic studies by the groups of Fu, Vicic, Weix, and others, all suggest a Ni I /Ni III catalytic cycle is involved in such transformations. However, we found that a nickel‐catalyzed cross‐coupling between aryl electrophiles and alkyl electrophiles could also favor a Ni 0 /Ni II catalytic cycle …”
Section: Figurementioning
confidence: 92%
“…It is important to note that previous mechanistic studies by the groups of Fu, Vicic, Weix, and others, all suggest a Ni I /Ni III catalytic cycle is involved in such transformations. However, we found that a nickel‐catalyzed cross‐coupling between aryl electrophiles and alkyl electrophiles could also favor a Ni 0 /Ni II catalytic cycle …”
Section: Figurementioning
confidence: 92%
“…31 Nicolas et al examined the oxidative addition of chloroarenes to [Ni(η 2 -C 6 H 5 Me)(dcpp)], in the context of nickel-catalysed Negishi cross-coupling reactions, using experimental and computational methodology (dcpp = 1,3-bis(dicyclohexylphosphino)propane). 32 [NiCl(Ar)(dcpp)] complexes were observed experimentally. Oxidative addition via a concerted transition state was found to have a rather low activation energy (ΔG ‡ = 12.9 kcal mol −1 ), with either transmetalation or the exchange of biaryl for chloroarene found to be the most energetically-demanding step.…”
Section: Reactions With Aryl Halidesmentioning
confidence: 99%
“…This mechanism differs from that established for [Pd(PPh 3 ) 4 ], which proceeds via [Pd(PPh 3 ) 2 ] and a concerted three‐centre transition state 17. Concerted three‐centre transition states have been computationally characterised for oxidative addition to Ni 0 complexes bearing bidentate phosphine ligands 9, 12, 14, 18, 19, 20. We present evidence from computational studies that Ni I and Ni II products both do indeed arise via [Ni(PEt 3 ) 3 ]; Ni I is obtained via an open‐shell singlet transition state and Ni II is formed from an S N 2‐type oxidative addition event (Figure 1 (b)).…”
Section: Introductionmentioning
confidence: 99%